2020
DOI: 10.3390/v12091028
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of the Bean-Associated Cytorhabdovirus by the Whitefly Bemisia tabaci MEAM1

Abstract: The knowledge of genomic data of new plant viruses is increasing exponentially; however, some aspects of their biology, such as vectors and host range, remain mostly unknown. This information is crucial for the understanding of virus–plant interactions, control strategies, and mechanisms to prevent outbreaks. Typically, rhabdoviruses infect monocot and dicot plants and are vectored in nature by hemipteran sap-sucking insects, including aphids, leafhoppers, and planthoppers. However, several strains of a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 61 publications
2
22
0
Order By: Relevance
“…The L protein-like TSA sequences included in the assembly of the BeTaV1 genome were previously reported to be 95–98% identical to soybean blotchy mosaic virus partial L gene sequences [18]; thus, it is tempting to speculate that the plant host of BeTaV1 may be soybeans. Recently, it was reported that the bean-associated cytorhabdovirus is efficiently transmitted by whiteflies, which was the first report of a whitefly-transmitted rhabdovirus [64], thus supporting our hypothesis that soybean blotchy mosaic virus may represent the second whitefly-transmitted rhabdovirus.…”
Section: Discussionsupporting
confidence: 88%
“…The L protein-like TSA sequences included in the assembly of the BeTaV1 genome were previously reported to be 95–98% identical to soybean blotchy mosaic virus partial L gene sequences [18]; thus, it is tempting to speculate that the plant host of BeTaV1 may be soybeans. Recently, it was reported that the bean-associated cytorhabdovirus is efficiently transmitted by whiteflies, which was the first report of a whitefly-transmitted rhabdovirus [64], thus supporting our hypothesis that soybean blotchy mosaic virus may represent the second whitefly-transmitted rhabdovirus.…”
Section: Discussionsupporting
confidence: 88%
“…Except for the 3′/N region, the P3/P4 region, which does not have the conserved consensus sequences, and the region L/5′ that had 12 of the 17 conserved nucleotides, all the intergenic regions have the highly conserved sequence 3′-TAAGAAAAACYGGGAKC-5′ ( Figure S5B ). BaCV-CN3 is closely related to the cytorhabdovirus BaCV strain BaCV-BR-GO ([ 26 ], GenBank accession MK202584], BaCV-LUZ ([ 27 ], GenBank accession MT811775), and Papaya cytorhabdovirus (PpVE) from Ecuador ([ 28 ], GenBank accession MH282832] ( Figure S5C ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the high nucleotide sequence identity between the cytorhabdovirus BaCV-BR-GO and PpVE, it was proposed that the virus species would be named Papaya cytorhabdovirus with strains PpVE infecting papayas and BaCV infecting beans [ 45 ]; thus, BaCV-CN3 is likely a strain of BaCV since it infects common bean and is closely related to the strains BaCV-BR-GO, BaCV-LUZ, as shown in the phylogenetic tree based on the RdRp amino acid sequences ( Figure S1C ). The vector of PpVE is unknown, and although BaCV is the first rhabdovirus reported to be transmitted to common beans by whitefly B. tabaci MEAM1 [ 27 ], the transmissibility of BaCV-CN3 by this vector was not determined. The symptoms induced by BaCV-CN3 could neither be confirmed because the sample from which it was identified was co-infected with BCMNV (GenBank accession MK069983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insects are significant drivers of virus emergence, as featured in submissions by Pinheiro-Lima et al, “ Transmission of the Bean-Associated Cytorhabdovirus by the Whitefly Bemisia tabaci MEAM1 ” [ 10 ], and Schoeny, et al, “ Can Winged Aphid Abundance Be a Predictor of Cucurbit Aphid-Borne Yellows Virus Epidemics in Melon Crop? ” [ 11 ].…”
mentioning
confidence: 99%